Remediation of Emerging Pollutants in Contaminated Wastewater and Aquatic Environments: Biomass‐Based Technologies. Issue 5 (17th March 2017) - Ncibi, Mohamed Chaker; Mahjoub, Borhane; Mahjoub, Olfa; Sillanpää, Mika
Abstract : The emergence of new kinds of pollutants including pharmaceuticals drugs, endocrine disrupting compounds, radionuclides, flame retardants, surfactants, and microbial toxins, to name a few, is posing new and serious challenges to the conventional wastewater treatment techniques, to the extent that the treatment plants are becoming indirect source of pollution. Thus, in order to meet these new environmental threats, tremendous research, and development efforts were and are being made to optimize the efficiency of several remediation techniques. In this review, recent and valuable research works will be presented and discussed concerning the remediation of emerging pollutants in contaminated wastewaters and aquatic environments through biomass‐based technologies, including bio‐adsorption using both terrestrial and marine bioresources and agro‐industrial wastes along with derived activated carbons. Phytoremediation, microbial remediation using bacteria, fungi, yeasts was also reported, in addition to some interesting combination scenarios such as biodegradtion/filtration, adsorption/biodegradation, and adsorption/ozonation. Eco‐friendliness, efficiency, cost‐effectiveness were the main criteria of choice among the rich literature, in order to prove that renewable biomass and its derived products could be the "sustainable core" for single or hybrid water treatment techniques, targeting emerging pollutants. Abstract : Facing the multitude of organic and inorganic pollutants of emerging concern threatening aquatic environments, several research studies are carried out to mitigate or remediate this serious problem. This review focuses on biomass‐based decontamination procedures as one of the most promising water treatment techniques. Indeed, various kinds of natural resources are industrially valorized worldwide for the development of efficient, yet eco‐friendly, depollution processes.